单位球上μ-Bloch空间到Zygmund型空间的加权Cesàro算子 - 赵艳辉 (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2016)
Supposing that α>0,let g be holomorphic functions in the unit ball B and µ(r) be a normal function on [0,1). Some questions of extended Cesàro operators are studied from µ-Bloch spaces to Zygmund type spaces in the unit ball. By the methods of functional analysis and several complex variables,the necessary and sufficient conditions are given for extended Cesàro operators Tg to be bounded and compact from µ-Bloch spaces to Zygmund type spaces.